The Racial Gap in Voting Among Women: White Women, Racial Resentment, and Support for Trump. Issue 4 (2nd October 2017) - Tien, Charles
Abstract: In this article, the question I answer is why did so many white women vote for Donald Trump? I reexamine the gender gap in voting to answer this question and to better understand the 2016 election results. The gender gap in voting and party identification is a real political phenomenon; the question remains to determine what kind of phenomenon it is. I advance the discussion by examining the racial component of the gender gap, show that there is a racial gap in the voting gender gap, and examine the sources of support for Donald Trump and other Republican candidates among white women using 2016 American National Election Studies Pilot Study data. I find that support for Republican candidates including most especially Donald Trump was surprisingly strong in 2016 among white women, and the source of that support showed to have a strong racial component.